Domestic violence against women: Reason and Remedy - Gehlot, Dr. Shailendra (International Journal of Psychosocial Rehabilitation, 2020)
Crime against women is a global problem but as we seein India, Not a single day passes without some report in Indian newspapers about some form of violence, abuse and ill--treatment of women and girls. The ill treatment and torture of wives for minor things, repeated teasing, sexual harassment, rapes, and murders have become a regular feature of our newspapers. Headlines such as ‘Woman Killed by her Husband by Kerosene’, or ‘Woman Burnt to Death in the Bathroom’, ‘Woman Found Hanging’ etc. are becoming common among Indian Society. Dowry death is often only the end result of experiences of domestic violence faced by the victim. Yet, it is usually only after a death takes place that the young woman’s parents or other relatives take note of the issue. Women victims are hesitant to discuss domestic violence with the paternal family. Even when the family is aware of the violence taking place, they do not seem to intervene. Frequently family members feel helpless to stop the abusive husband. For their part, victims refuse to talk about domestic violence because they look upon this as bringing embarrassment to their husbands. Personally, for them, it means admitting to a failure of their relationship. Very rarely do they talk to or seek external help because they have been socialized to be the carrier of the family honor. This isolation means that their suffering from shame, guilt, fear, abandonment and the suffering from the immediate acts of domestic violence are committed in the privacy of homes and by a person on whom the victim is economically and emotionally dependent. For society, accepting the fact of domestic violence would be really shameful and an unpleasant fact that what is considered to be one of its most precious institutions is also one of its most dangerous and vulnerable. From the below diagram, we can see that out of all the crimes against women, cruelty by husband and relatives stands highest. The Figure shows that Crimes against women per cent distribution 2013 not a single day passes without some report in Indian newspapers about some form of inhumane treatment of women and girls. The ill-treatment and torture of wives for trivial things, repeated teasing, sexual harassment, rapes, and murders have become a regular feature of our newspapers.